Lifted Skin Fold (LSF) Technique as an Effort to Reduce Insulin Injection Pain - Iswatun Qasanah; Diana Tri Lestari; Tukiyo; Sukamto (Program Studi S1 Keperawatan Universitas Ngudi Waluyo, 2025)
Diabetes mellitus (DM) is a serious threat to global health and is one of the top ten causes of death in the world. DM patients face challenges in undergoing therapy, especially due to pain and discomfort during insulin injection. This condition often causes refusal of treatment, which has a negative impact on therapy compliance and quality of life. The purpose of this study was to determine the effect of the LSF technique on the level of pain during insulin injection. This study employed a quasi-experimental research design with a pre-posttest design. The sample size was 120 inpatients who met the inclusion criteria of being DM patients with good awareness and willing to be respondents, and the exclusion criteria of being DM patients who could not read and write and were unwilling to be respondents. The sampling technique used in this study was total sampling. The research instruments used were a demographic questionnaire, NRS (Numeric Rating Scale) pain scale, and LSF technique SOP. Data analysis used the Wilcoxon Test and Mann Whitney Test. The study results showed that the pre-test pain level of the intervention group had a median value of 3, and the post-test became 2. The pre-test pain level of the control group had a median value of 3, and the post-test remained at 3. The results of the Wilcoxon test for the intervention group were p = 0.000, while the control group was p = 0.160. The results of the Mann Whitney test obtained p = 0.000. There was a significant difference in the level of pain pre-test post-test in the intervention group. There was no difference in the level of pain pre-test post-test in the control group. There was an effect of the LSF technique on the level of pain in insulin injection. This study recommends that the LSF technique can be one of the options to reduce pain when injecting insulin.